NHG Eye Institute-Khoo Teck Puat Hospital 3rd Quality Day - Wan Hazabbah, Wan Hitam (Pusat Pengajian Sains Perubatan, 2010)
• USM CEC Program is to recognize & reinforce the importance of eradicating preventable blindness prevention of blindness through eye screening program promotion of eye health to reduce the risk of blindness in community educate the community of various blinding eye diseases & treatment options available creating awareness of the community of blinding diseases & ways of preventing or curing it